Pengaruh Lokasi Strategis dan Kualitas Pelayanan Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Pada RedDoorz near CBD Ciledug, Kota Tangerang, Provinsi Banten - Sulistiyo, Tri Djoko; Nurbaeti, Nurbaeti; Mariati, Sri; Mumin, Adhi Trirachmadi; Muhardiansyah, Doni (JURNAL BISNIS HOSPITALITI, 2024)
This research aims to determine the effect of strategic location and service quality on customer loyalty through customer satisfaction at Reddoorz Near CBD Ciledug. This research uses a path analysis method that explains the influence of the independent variable on the dependent variable through mediating variables. Data was collected through a Google Form questionnaire carried out by accidental sampling. The population is all visitors staying at RedDoorz near CBD Ciledug. The research sample consisted of 100 respondents. The research results are: (1) Strategic location and service quality have a significant effect on customer satisfaction; (2) Strategic location and service quality have a significant effect on customer loyalty; (3) Customer satisfaction has a significant effect on customer loyalty; (4) Strategic location and service quality have a significant effect on customer loyalty through customer satisfaction. RedDoorz near CBD Ciledug's strategic location provides easy access to business centers and essential facilities, significantly increasing customer satisfaction. High service quality at RedDoorz also plays a vital role in improving customer loyalty through satisfaction by guaranteeing tangibles, reliability, responsiveness, assurance, and empathy. As a result, the combination of strategic location and superior service quality creates positive customer relationships that are strong and sustainable in the long term.